Auditory temporal resolution and evoked responses to pulsed sounds for the Yangtze finless porpoises (Neophocaena phocaenoides asiaeorientalis) - Mooney, T.; Li, S.; Ketten, Darlene; Wang, K.; Wang, D. (Springer, 2011)
Temporal cues are important for some forms of auditory processing, such as echolocation. Among odontocetes (toothed whales, dolphins, and porpoises), it has been suggested that porpoises may have temporal processing abilities which differ from other odontocetes because of their relatively narrow auditory filters and longer duration echolocation signals. This study examined auditory temporal resolution in two Yangtze finless porpoises (Neophocaena phocaenoides asiaeorientalis) using auditory evoked potentials (AEPs) to measure: (a) rate following responses and modulation rate transfer function for 100 kHz centered pulse sounds and (b) hearing thresholds and response amplitudes generated by individual pulses of different durations. The animals followed pulses well at modulation rates up to 1,250 Hz, after which response amplitudes declined until extinguished beyond 2,500 Hz. The subjects had significantly better hearing thresholds for longer, narrower-band pulses similar to porpoise echolocation signals compared to brief, broadband sounds resembling dolphin clicks. Results indicate that the Yangtze finless porpoise follows individual acoustic signals at rates similar to other odontocetes tested. Relatively good sensitivity for longer duration, narrow-band signals suggests that finless porpoise hearing is well suited to detect their unique echolocation signals